2013
DOI: 10.1007/s00484-013-0756-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects on growth phenology of co-occurring Eucalyptus species

Abstract: Growth is one of the most important phenological cycles in a plant's life. Higher growth rates increase the competitive ability, survival and recruitment and can provide a measure of a plant's adaptive capacity to climate variability and change. This study identified the growth relationship of six Eucalyptus species to variations in temperature, soil moisture availability, photoperiod length and air humidity over 12 months. The six species represent two naturally co-occurring groups of three species each repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…; Rawal et al. , ,b, ). The combined effect of habitat fragmentation and climate changes may be decreased abundance, increased spatial heterogeneity, and increased asynchrony of nectar resources.…”
Section: Discussionmentioning
confidence: 96%
“…; Rawal et al. , ,b, ). The combined effect of habitat fragmentation and climate changes may be decreased abundance, increased spatial heterogeneity, and increased asynchrony of nectar resources.…”
Section: Discussionmentioning
confidence: 96%
“…Over the long term, climate‐mediated effects on phenology and growth may shift the competitive balance between species (Savage and Cavender‐Bares , Rawal et al. ), which in turn has the potential to influence species’ distributions (Chuine and Beaubien ). Future studies of tree species’ range limits should compare the phenology and reproductive success of mature stands within the range and near range margins and examine the focal species’ phenology and reproductive success relative to that of other competing species in the forest community.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no confirmation of the influence of photoperiod on LD in forest species, such as eucalyptus (Rawal et al, 2015). This information could help improving the quality of seedlings and increase the probability of success in the implantation and establishment of forests (Martins et al, 2007;Rawal et al, 2014;Ferreira et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…One of the ways to identify the influence of photoperiod is through field experiments with several sowing dates throughout the year (Rosa et al, 2009). Some studies have reported the effect of photoperiod on the flowering and germination of woody species (Rawal et al, 2014). However, there is no confirmation of the influence of photoperiod on LD in forest species, such as eucalyptus (Rawal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%